Bodies of the Future in Ideal Societies: Representations of Eugenics in Brazilian Modernist Literature - Queluz, Gilson Leandro (Circumscribere International Journal for the History of Science, 2008)
This article aims at analyzing the representations of eugenics in two utopian novels of Brazilian modernist literature: A Amazônia Misteriosa (1925) by Gastão Cruls and O Presidente Negro ou o Choque das Raças (1926) by Monteiro Lobato. Diverse and contradictory, these representations are proposals for radical and aesthetic eugenics, shaping a dense arena where fictional narratives fight each other to lure readers into certain views on nationality and science.